ChemInform Abstract: Luminescent Materials: Locking π‐Conjugated and Heterocyclic Ligands with Boron(III). Issue 20 (20th May 2014) - Frath, Denis; Massue, Julien; Ulrich, Gilles; Ziessel, Raymond
Abstract Review: 154 refs.